On the Relation of Microstructure and Texture Evolution in an Austenitic Fe-28Mn-0.28C TWIP Steel During Cold Rolling - Haase, Christian; Chowdhury, Sandip Ghosh; Barrales-Mora, Luis A.; Molodov, Dmitri A.; Gottstein, Günter (Metallurgical and materials transactions. A, Physical metallurgy and materials science, 2013)
In the present study, microstructure and texture evolution in an austenitic Fe-28 wt pct Mn-0.28 wt pct C TWIP steel in the range between 10 and 80 pct reduction by cold rolling were systematically analyzed. The formation of the observed microstructural features occurred in three different stages: I (10 to 20 pct)—mainly slip lines, grain elongation, and formation of few twin-matrix lamellae; II (30 to 50 pct)—severe increase of the volume fraction of twins, alignment of twins with the rolling plane, and formation of microshear bands; and III (60 to 80 pct)—further alignment of twins, evolution of a herring bone structure, and macroshear bands. In contrast to most f.c.c. metals, the transition from Copper- to Brass-type texture occurred at low strain levels (30 pct). This behavior is attributed to the early formation of deformation twins in the material and can be related to the SFE of this high manganese steel. At higher reduction levels, microscopic (≥40 pct) and macroscopic shear band formation (≥60 pct) contributed to the increase of randomly oriented grains, mainly at the expense of the Brass component. Furthermore, the formation of the Goss component and of the 〈111〉//ND fiber (γ) is attributed to severe twin formation.